2004
DOI: 10.1590/s0004-282x2004000500007
|View full text |Cite
|
Sign up to set email alerts
|

A longitudial study of a neuropsychological rehabilitation program in Alzheimer's disease

Abstract: Our aim was to study the duration of benefits derived from a neuropsychological rehabilitation program (NRP) for dementia patients. METHOD: The participants in this study were three patients diagnosed as probable Alzheimer's disease in the initial-to-moderate phase; the three were taking anticholinesterases. They were submitted to a neuropsychological evaluation (NE) before the NRP and then revaluated after 12 and 24 months of treatment. The aim of our intervention was to do practical work with implicit and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…In previous studies, preserved implicit memory in persons with dementia has been reported (Baird & Samson, 2009;Kessels et al, 2005;Machado et al, 2009). However, it was difficult to learn new things for persons with dementia even using implicit memories (Abrisqueta-Gomez et al, 2004;van Tilborg et al, 2011;White et al, 2004). Another study reported that the visual information passively provided was memorized for spatial recognition (Kessels et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, preserved implicit memory in persons with dementia has been reported (Baird & Samson, 2009;Kessels et al, 2005;Machado et al, 2009). However, it was difficult to learn new things for persons with dementia even using implicit memories (Abrisqueta-Gomez et al, 2004;van Tilborg et al, 2011;White et al, 2004). Another study reported that the visual information passively provided was memorized for spatial recognition (Kessels et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…Based on evidence for preserved implicit memory, training in daily life activities using implicit memory has been carried out (Abrisqueta-Gomez et al, 2004;van Tilborg et al, 2011;White et al, 2004). Those previous studies led to rehabilitation programs to nurture new motor and cognitive skills in daily life activities in the elderly with dementia, and implicit stimulation was used to facilitate learning of the skills in rehabilitation settings (Abrisqueta-Gomez et al, 2004;van Tilborg et al, 2011;White et al, 2004). They concluded that there was an effect of implicit memory on the training (Abrisqueta-Gomez et al, 2004;White et al, 2004), and there remained a possibility in elderly with dementia to acquire new skills (van Tilborg et al, 2011).…”
Section: Effects Of Environmental Stimulation On Demented Elderlymentioning
confidence: 99%
See 2 more Smart Citations
“…As with any country, Brazil also has a growing older population of people with LD, including those with dementia (Abrisqueta-Gomez et al, 2004). Caldas and Berterö (2007) argue that the concept of ageing needs to be reframed especially when it comes to those with LD, since their functional decline requires particular and intensive support.…”
Section: Responsibility For Carementioning
confidence: 99%